Upgrade the Students’ Speaking Ability: Implementation of the Callan Method at the Second Grade Students High School - Ismail, Hamid; Saiful (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The primary goal of the research is to determine the student's accuracy and fluency in speaking by using the calling method. The researcher gathered the data using a pre-experimental design. There were 54 students in the second grade at High School Muhammadiyah Ternate who made up the research population. We used 25 students as the research sample. The oral examination method was used by the researcher to gather data. The research's data analysis showed that after using the Callan Method to teach the students, their speaking abilities significantly improved. It was demonstrated by the outcome of the statistical analysis of the data analysis, which showed that the t-test value was 3.65 and the t-table value was 2.063, with 3.65 > 2.063, at the level of significance 0.05 with degree of freedom (Df = 24). The first-graders at high school Muhammadiyah Ternate have good speaking skills.